Compact, wideband impedance tuner using a three‐line‐microstrip structure. Issue 9 (1st May 2018) - Heredia, J.; Ribó, M.; Pradell, L.
Abstract : A novel three‐line‐microstrip compact impedance tuner is presented. It is based on a multimodal structure wherein six variable capacitances, implemented with two parallel‐connected varactors each, create multiple interactions among the three‐line‐microstrip modes in a reduced circuit area. Experimental results show better‐than‐70% coverage of the Smith chart in an 85% frequency bandwidth from 1.4 to 3.2 GHz.